Allostatic stress load and CMV serostatus impact immune response to maximal exercise in collegiate swimmers - Theall, B.; Wang, H.; Kuremsky, C. A.; Cho, E.; Hardin, K.; Robelot, L.; Marucci, J.; Mullenix, S.; Lemoine Jr., N.; Johannsen, N. M.; Irving, B. A.; Spielmann, G. (Journal of Applied Physiology, 2019)
Collegiate athletes are exposed to varying levels of academic and physical stressors, placing them at increased risk for stress-activated latent viral infections. However, the impact of allostatic stress load on the immune response to maximal exercise in athletes remains largely unknown. This study examined the effects of a 7-mo training period and cytomegalovirus (CMV) serostatus on immune cell response to high-intensity swim tests within a group of collegiate swimmers. Samples were collected from 15 National Collegiate Athletic Association Division I swimmers (9 men, 6 women: 19.87 ± 0.64 yr) before and after exhaustive in-pool swims at 2 time points (V1: immediately post-season 1 and V3: beginning of season 2). An additional off-season (V2) time point was collected in a subset of 9 swimmers. Natural killer (NK) cell, B cell, and T cells were quantified by flow cytometry. Linear mixed models were used to determine the effects of exercise, time point, and CMV serostatus (alpha = 0.05). Resting senescent CD8+ T cells were higher in CMV-seropositive participants at V3 (P = 0.005). CMV-seronegative participants had a decrease in resting senescent CD8+ T cells from V1 to V3 (P = 0.021). After acute exercise, CMV-seropositive participants had lower naïve CD8+ T cells (P < 0.001) and higher senescent CD8+ T cells (P < 0.001). Increased cumulative stress levels did not appear to affect B-cell and NK-cell compartments. Immune response to exercise was impacted by CMV serostatus and allostatic stress load. Young CMV-seropositive athletes exposed to elevated stressors should be monitored to determine long-term effects of training and academic stressors. NEW & NOTEWORTHY Allostatic stress load is associated with impaired immune response to maximal exercise in cytomegalovirus (CMV)-seropositive subjects but not in CMV-seronegative young healthy adults.